Optimal reservoir operation for water supply in dry season: the case study of Cua Dat reservoir in the Chu Ma river system Thanh Hoa province :Thesis of master degree: Major: Integrated Water Resources Management - Trinh, Xuan Manh (Thuy Loi University, 2020)
This research is done for the partial fulfilment of requirement for Master of Science Degree at Thuy loi University (This Master Programme is supported by NICHE - VNM 106 project)